Association of Calcium and Phosphate Levels with Incident Chronic Kidney Disease in Patients with Hypoparathyroidism: A Retrospective Case-Control Study. (2nd November 2022) - Gosmanova, Elvira O.; Ayodele, Olulade; Chen, Kristina; Cook, Erin E.; Mu, Fan; Young, Joshua A.; Rejnmark, Lars
Abstract : Objective . Reasons for the increased incidence of chronic kidney disease (CKD) in patients with chronic hypoparathyroidism are poorly understood. This study evaluated associations between levels of albumin-corrected serum calcium, serum phosphate, and calcium-phosphate product and the odds of CKD development in patients with chronic hypoparathyroidism. Design . A retrospective nested case-control study of adult patients with chronic hypoparathyroidism who had ≥1 prescription for calcitriol who developed CKD and matched controls who did not develop CKD were selected from the IBM® Explorys electronic medical record database. Patients . The study included a cohort of 300 patients for the albumin-corrected serum calcium analysis and 80 patients for the serum phosphate and calcium-phosphate product analyses. Measurements . We examined associations between albumin-corrected serum calcium, serum phosphate and calcium-phosphate product levels, and the risk of devloping CKD (defined as ≥2 outpatient estimated glomerular filtration values <60 mL/min/1.73 m 2 occuring ≥3 months apart or ≥1 diagnostic code for CKD stages 3–5). Results . Individuals who had ≥67% of albumin-corrected serum calcium measurements outside, above, or below the study-defined range (2.00–2.25 mmol/L [8.0–9.0 mg/dL]) had 3.5-, 2.9-, and 2.7-fold higher odds of developing CKD (adjusted odds ratios [95% CI]: 3.46 [1.82–6.56], 2.85 [1.30–6.28], and 2.68 [1.16–6.15]), respectively, compared with patients who had <33% of albumin-corrected calcium measurements in those ranges. There was no association between developing CKD and having any serum phosphate measurements or any calcium-phosphate product measurements above normal population ranges. Conclusion . In adult patients with chronic hypoparathyroidism, a higher proportion of albumin-corrected calcium measurements outside of the 2.00–2.25 mmol/L (8.0–9.0 mg/dL) range was associated with higher odds of developing CKD.